Geopolitical Strategies In Maritime Policy: Implications For Security And Stability In The Indo-Pacific Region - Sarjito, Aris (Policy and Maritime Review, 2024)
The Indo-Pacific region is a critical geopolitical arena, shaped by strategic competition, territorial disputes, and economic interdependence. This research examines the risks and opportunities for maintaining stability in the region, focusing on the implications of major stakeholders' strategies, such as China’s Belt and Road Initiative, the U.S. Indo-Pacific Strategy, and ASEAN’s regional policies. Using a qualitative approach based on secondary data, the study analyzes policy documents, reports, and academic literature to uncover key dynamics influencing regional security. The findings highlight significant risks, including rising tensions between major powers, fragmented ASEAN cohesion, and vulnerabilities to non-traditional threats such as cyberattacks and climate change. Conversely, opportunities exist through multilateral cooperation, economic integration, and technological innovations that enhance maritime security and sustainability. The research concludes that achieving stability requires balancing power dynamics, fostering inclusive dialogue, and addressing shared challenges collaboratively. By leveraging economic and technological tools while promoting transparency and trust, the Indo-Pacific can navigate its complexities to secure a stable and prosperous future. Keywords: geopolitical strategies, Indo-Pacific, multilateral cooperation, regional stability